The current status of the clinical utility of liquid biopsies in cancer. (2nd November 2019) - Snow, Anson; Chen, Denaly; Lang, Julie E.
ABSTRACT: Introduction : Liquid biopsies have attracted considerable attention as potential diagnostic, prognostic, predictive, and screening assays in oncology. The term liquid biopsies include circulating tumor cells (CTCs) and circulating tumor DNA (ctDNA) in the blood. While many liquid biopsy technologies are under active investigation, relatively few liquid biopsy assays have been proven to serve as a diagnostic surrogate for biopsies of metastatic disease as predictive biomarkers to guide the selection of therapy in the clinic. Areas covered : The objective of this review is to highlight the status of liquid biopsies in solid tumors in the oncology literature with attention to proven utility as diagnostic surrogates for macrometastases. Expert opinion : Carefully designed clinical-translational studies are needed to establish the diagnostic accuracy and clinical utility of liquid biopsy biomarkers in oncology. Investigators must fully consider relevant pre-analytical variables, assay sensitivity, bioinformatics considerations as well as the clinical utility of rare event profiling in the context of the normal blood background. Future liquid biopsy research should address the concern that not all DNA mutations are expressed and should provide the means to discover potential therapeutic targets in metastatic patients via a minimally invasive blood draw.